Freakish Masculinity in the Eighteenth Century: Andrew Miller’s Ingenious Pain and Hilary Mantel’s The Giant, O’Brien - Lavoie, Chantel (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2022)
This paper considers masculinity in two twentieth-century historical novels set in the eighteenth century: Andrew Miller’s Ingenious Pain (1997) and Hilary Mantel’s The Giant, O’Brien (1998). It argues that both novels create protagonists who embody masculine-coded attributes, including resistance to pain and bodily size and strength, and that, in both novels, earning potential is concomitant with such attributes. Complicating matters, however, the very exaggeration of stereotypical masculine characteristics in these texts causes each man to seem something other and less than a man—ranging for both, at different times, from monstrous to pathetically weak (and childlike, or even womanish) victim. Qualities associated with manhood, therefore, paradoxically deny the men more agency than they allow in these stories set in the eighteenth century, inhibiting them from enjoying ideal manhood and making them the property of other men.